Analisis Profitabilitas Usahatani Bayam Jepang Tersertifikasi Organik di Kecamatan Getasan Kabupaten Semarang - Prasetyo, Dimas Adhi; Roessali, Wiludjeng; Santoso, Siswanto Imam (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The purpose of this study was to analyze the profitability and factors affecting Japanese spinach farming in Getasan District, Semarang Regency. The research location was determined purposively. The research was conducted from September to November 2024 in Getasan District, Semarang Regency. The research method used was survey. Data collection techniques were conducted by interview using open and closed questionnaires. The sampling method used probability sampling with multistage random sampling technique. The number of respondents used was 52 Japanese spinach farmers who had joined farmer groups and were organically certified. The types of data used are primary and secondary. Data analysis methods used are production costs, revenue, income, profitability. Scoring analysis method was conducted for managerial ability variables and agribusiness partnerships. The test analysis used is one sample t-test and multiple linear regression. Based on the results of the study, it was found that the average income of farmers was Rp. 1,101,405. The profitability obtained is 109.82%. The one sample t-test results show that Japanese spinach farming is profitable for farmers. Regression test results show that all independent variables simultaneously affect profitability. Variables that partially affect profitability are the amount of production, selling price and profitability.